Influência do período de molhamento, temperatura e concentração de inóculo de Pyricularia grisea na ocorrência da brusone em plântulas de trigo - Storani, Waleska Del Pietro (2013)
Blast disease, caused by Magnaporthe grisea (anamorph Pyricularia grisea), is one of the main diseases of wheat and is disseminated throughout main producing states of the Country. It has been causing significant yield loss and is a limiting factor for the crop s expansion in central Brazil where the weather is highly favorable. The use of resistant cultivars can be influenced by weather conditions and concentration of inoculum. Chapter 1 of the present dissertation describes the influence of period of foliar wetness on the occurrence of blast in wheat seedlings in two experiments. The first one employed cultivars BH1146 (resistant) and BR40 (susceptible) inoculated with the Pyricularia isolate PR06- 03. In the second assay, the cultivars were BR18 (resistant) and Anahuac (susceptible) inoculated with the fungal isolate PR01-23. Five treatments were the period of wetness (6, 10, 14, 18 and 24h) in ten replications. Analysis was performed using a completely randomized design with a factorial plan of the treatments (five foliar wetness periods and 2 cultivars). Results showed that the minimum period needed for the development of the disease was 10 hours when inoculated with the isolate PR06-03. The longer the foliar wetness period the higher the incidence and severity of the disease regardless the resistance of cultivars. Chapter 2 aimed to determine the influence of the weather and concentration of P. grisea on the incidence and severity of blast. The experiment used totally randomized design with a factorial plan of the treatments: four concentrations (10³, 104, 105, 106 spores/ml) and two cultivars, ten repetitions. The wheat cultivars were BR18 (resistant) and Anahuac (susceptible) which were inoculated with 50ml of P. grisea suspension (isolate PR06-03) at the concentrations 10³, 104, 105, 106 spores/ml. The seedlings were submitted to temperatures of 22ºC and 28ºC for 18 hours of foliar wetness. The results showed that at 22ºC higher disease severity occurred on susceptible cultivar whereas the disease was the same for both cultivars at 28ºC. The resistant cultivar reacted like a susceptible when submitted to high temperature and high concentration of pathogen.